2019
DOI: 10.18593/abh.19211
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the watsu method on functional capacity, anxiety and depression in patients with parkinson disease

Abstract: Parkinson's disease (PD) is a chronic and progressive pathology that results from the degeneration of the black substance responsible for the voluntary control of movements. The reduction of dopamine generates motor and non-motor symptoms that hinder the mobility of the patient and the execution of their activities of daily living. The Watsu method relieves pain, tension and releases the muscles, fascias and spine leading to the gain of flexibility and range of motion, and can be a facilitator in reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The five articles included in the meta-analysis on mental effects (with a total of 78 participants, 62 of them receiving WATSU) reported comparable quantitative data related to fibromyalgia [8,57,58], neurological disorders [61], and pregnancy [9]. Mental effects were assessed by the Mental Health Subscale of the SF-36 [8,58], the Geriatric Depression Inventory (GDI 15) [57], the Beck's Depression Inventory (BDI) [61], and VAS (stress) [9]. The overall effect size was Hedges's g = -0.68 (95% CI = -1.02 to -0.35) in favor of WATSU (Fig 4).…”
Section: Meta-analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…The five articles included in the meta-analysis on mental effects (with a total of 78 participants, 62 of them receiving WATSU) reported comparable quantitative data related to fibromyalgia [8,57,58], neurological disorders [61], and pregnancy [9]. Mental effects were assessed by the Mental Health Subscale of the SF-36 [8,58], the Geriatric Depression Inventory (GDI 15) [57], the Beck's Depression Inventory (BDI) [61], and VAS (stress) [9]. The overall effect size was Hedges's g = -0.68 (95% CI = -1.02 to -0.35) in favor of WATSU (Fig 4).…”
Section: Meta-analysesmentioning
confidence: 99%
“…The remaining 20 studies reported on repeated measure designs involving within-group comparisons (14 case series, CSs [13,[54][55][56][57][58][59][60][61][62][63][64][65] including a collection of narrative retrospective reports [21]), and on single cases (6 CRs) [11,[31][32][33][34][35]. Tools chosen for assessment of the effects of WATSU considered physical and mental aspects.…”
Section: Study Designs and Assessmentsmentioning
confidence: 99%
See 3 more Smart Citations